Nuclear Back-end and Transmutation Technology for Waste Disposal: Beyond the Fukushima Accident - Nakajima, Ken (Springer Nature, 2015)
Effects of Radiation/Radiation Protection; Nuclear Engineering; Particle and Nuclear Physics; Waste Management/Waste Technology; Industrial Pollution Prevention; Nuclear fuel cycle; Environmental radiation; Nuclear transmutation; Accelerator-driven systems (ADS); Nuclear reactor; Radioactive wastes